Systematic review of bike simulator studies - Ansariyar, A.; Sadeghvaziri, E.; Jeihani, M. (Journal of Science and Cycling, 2022)
The bicycle is a promising, human-powered and emission-free transportation mode that is being increasingly advocated for due to its significant positive impact on congestion and the environment. Despite the growing popularity of bicycles as a sustainable transport mode in the past two decades, compared to the vehicular mode, bicycle facilities have relatively less development, research, and understanding. In recent years, the bike simulator (BS) provides a fairly realistic environment for conducting research in the area of cycling, and it is capable of simulating real-world environments. It has the potential to contribute to the understanding of bicycle facility design and cyclist`s behavior. This study is designed to identify and review BS studies, evaluate the study approaches used in the literature, and uncover their gaps and challenges. After reviewing the literature, four approaches were identified: "application of BS to suggest a mathematical dynamic model/equation for bicycle/bicyclist stability," "incorporation of BS with virtual reality (VR) technology," "application of a BS in safety promotion studies," and "application of BS in medical, psychology, sports management, and other branches of science." This review is expected to assist researchers and decision makers with selecting the most appropriate quantification method based on their goals and study limitations. Compared to the car simulator, fewer studies have been conducted on BSs. Therefore, future research is needed to address the identified challenges in the BS evaluation process.